Study on the synergies and trade-offs of sectoral water use and their relationship with economic development - Jianqin Ma; Shuoguo Yang; Qing Wu; Xiuping Hao; Bifeng Cui; Zhihong Su (PLoS ONE, 2025)
Water scarcity is dynamic and complex, beyond geophysical stressors and responses, it is critical to also consider how multi-sector, multiscale economic teleconnections mitigate or exacerbate water shortages. This study analyzes the spatial and temporal characteristics of Water Footprint (WF) in China from 2005 to 2022 and their relationship with economic development. The findings reveal an overall increase in China’s WF, with the fastest growth observed in the Northwest and Northeast regions. Notably, Heilongjiang, Inner Mongolia, and Xinjiang experienced significant increases, while Zhejiang, Beijing, and Chongqing saw declines. Agricultural water footprint (WFargi) account for the largest share, while industrial water footprint (WFindu) show a decreasing trend, indicating improved water-use efficiency in industry. However, the rise in contamination water footprint (WFcont) and significant spatial disparities in import water footprint (WFimport) and export water footprint (WFexport) highlight the challenges in water resources management. Across different regions, there is a strong synergy between agricultural and ecological water use, while a notable trade-offs exists between industrial and agricultural water use, particularly in the Northeast. The relationship between WF consumption and economic development in China exhibits a phased pattern. From 2011 to 2016, most regions achieved strong decoupling, but from 2017 to 2022, all regions reverted to weak decoupling. This study provides new insights into the relationship between sectoral water use and economic development at regional and provincial levels, contributing to efforts to alleviate water scarcity, enhance water resources management, and promote sustainable economic development.